Gender and Green Governance : The Political Economy of Women's Presence Within and Beyond Community Forest - Agarwal, Bina (India Oxford University Press, 2015)
Using primary data from India and Nepal, this volume is the first major study to comprehensively address the issue of gender and the role of women in relation to environmental collective action and green governance. It traces women's history of exclusion from public institutions and looks at how constraints can be overcome.
Include Index and References
Keywords: Women in forestry -- Community forestry -- Nepal